Analisis Risiko Anemia Pada Ketuban Pecah Dini Berdasarkan Niat Kehamilan - Lizzeth Natalie Chandral; Kirana Anggraeni (Journal of Religion and Public Health, 2022)
Premature rupture of membranes (PROM) is an obstetric condition in which the membranes rupture spontaneously with the release of amniotic fluid at least one hour before delivery. This study is an analytical observational study with a cross-sectional design. The study was conducted on 124 mothers who gave birth at RSUP Dr. Kariadi in 2020. Pregnancy intention was assessed using a female questionnaire in the 2012 IDHS. The relationship between anemia in premature rupture of membranes based on intention to become pregnant was analyzed using the chi-square test with Fisher's exact test as an alternative test. The risk of anemia in premature rupture of membranes for each pregnancy intention was assessed by calculating the odds ratio. Mother who experience anemia is 2 times more risky on experiencing premature rupture of membranes than those who do not experience anemia in unwanted pregnancies. However, this cannot describe the population in total. There was no significant relationship between anemia and the incidence of premature rupture of membranes on unwanted, mistimed, and intended pregnancy.The prevalence of anemia in RSUP Dr. Kariadi was 72,8% in unwanted pregnancies, 41,1% in mistimed pregnancies, and 45,9% in intended pregnancies. Prevalence of premature rupture of membranes in RSUP Dr. Kariadi was 45,5% in unwanted pregnancies, 29,4% in mistimed pregnancies, and 43,8% in intended pregnancies. The incidence of anemia in premature rupture of membranes in RSUP Dr. Kariadi was 51,9%. Mothers with anemia were 2 times more likely to have an unwanted pregnancy, 0,25 times more likely to have a mistimed pregnancy, and 1,6 times more likely to have an intended pregnancy to have premature rupture of membranes than those without anemia. However, these results are not meaningful so they cannot represent the population as a whole.Keywords: Anemia, Premature Rupture of Membranes, Pregnancy Intentions, Unwanted PregnancyAbstrakKetuban Pecah Dini (KPD) merupakan kondisi obstetrik dimana terjadi pecahnya selaput ketuban secara spontan dengan keluarnya cairan ketuban setidaknya satu jam sebelum persalinan. Penelitian ini merupakan analitik observasional desain cross-sectional. Penelitian dilakukan terhadap 124 ibu yang melakukan persalinan di RSUP Dr. Kariadi tahun 2020. Niat kehamilan dinilai dengan menggunakan kuesioner pertanyaan wanita pada SDKI 2012. Hubungan anemia pada ketuban pecah dini berdasarkan niat kehamilan dianalisis dengan uji chi-square dengan uji fisher sebagai uji alternatif. Risiko anemia pada ketuban pecah dini untuk tiap niat kehamilan dinilai dari penghitungan odds ratio. Ibu dengan anemia 2 kali lebih berisiko untuk mengalami ketuban pecah dini dibandingkan yang tidak mengalami anemia pada kehamilan tidak diinginkan, namun tidak dapat mewakili populasi secara keseluruhan. Tidak didapatkan hubungan bermakna antara anemia dan kejadian ketuban pecah dini pada niat kehamilan tidak diinginkan, tidak direncanakan, dan diinginkan. Prevalensi anemia di RSUP Dr. Kariadi sebesar 72,8% pada kehamilan tidak diinginkan, 41,1% pada kehamilan tidak direncanakan, dan 45,9% pada kehamilan diinginkan. Prevalensi ketuban pecah dini di RSUP Dr. Kariadi sebesar 45,5% pada kehamilan tidak diinginkan, 29,4% pada kehamilan tidak direncanakan, dan 43,8% pada kehamilan diinginkan. Angka kejadian anemia pada ketuban pecah dini di RSUP Dr. Kariadi sebesar 51,9%. Ibu dengan anemia 2 kali lebih berisiko pada kehamilan tidak diinginkan, 0,25 kali lebih berisiko pada kehamilan tidak direncanakan, dan 1,6 kali lebih berisiko pada kehamilan diinginkan untuk mengalami ketuban pecah dini dibandingkan yang tidak mengalami anemia. Namun, hasil tersebut tidak bermakna sehingga tidak dapat mewakili populasi secara keseluruhan.Kata kunci: anemia, ketuban pecah dini, niat kehamilan, kehamilan tidak diinginkan